Glycine attenuates sepsis-induced white matter injury by modulating gut microbiota - Liu, Jingfei; Zhang, Li; Feng, Chunyang; Li, Ye; Wu, Huiling; Wang, Xueer; Li, Dong (Frontiers in Molecular Biosciences, 2026)
Sepsis poses a significant threat to preterm infants and is a leading cause of white matter injury (WMI); however, effective therapeutic strategies remain limited. Recent studies suggest that gut microbiota dysbiosis contributes to sepsis-induced systemic inflammation and neurological damage. After treating mice with LPS-induced sepsis with glycine, we evaluated pathological changes in the brain and ileum by HE staining and analyzed gut microbiota composition by 16S rRNA gene sequencing. Inflammatory cytokine levels in brain and ileal tissues were quantified by ELISA. Transcriptomic profiling was performed to identify differentially expressed genes and enriched pathways in the brains of septic mice with WMI. Additionally, protein expression levels of occludin, Iba-1, BMP, and C5aR1 were assessed by IHC and Western blotting. The study demonstrates that sepsis induces WMI. Glycine alleviated intestinal dysbiosis, restored the expression and function of intestinal tight junction proteins, and reduced pro-inflammatory cytokine levels in both ileal and brain tissues. Moreover, glycine attenuated microglial activation, as evidenced by decreased Iba-1 expression, and preserved myelin integrity by preventing the loss of MBP in the brain. Transcriptomic analysis revealed significant upregulation of C5aR1 in brain tissue associated with sepsis-induced WMI. Collectively, these findings indicate that glycine represents a promising therapeutic strategy for the prevention and treatment of sepsis-associated WMI, and that targeting the C5aR1-mediated complement pathway may offer a novel approach to mitigate neuroinflammation and white matter damage.